2018
DOI: 10.1111/iju.13848
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis as a predictor of transient exacerbation of overactive bladder symptoms after robot‐assisted laparoscopic radical prostatectomy

Abstract: Objectives To assess whether atherosclerosis is involved in the development of overactive bladder and the function of lower urinary tract after robot‐assisted radical prostatectomy. Methods The present cohort consisted of 80 consecutive participants. The preoperative cardio‐ankle vascular index was used to evaluate the presence of atherosclerosis. The present cohort was split into two groups, the atherosclerotic group, whose cardio‐ankle vascular index was ≥9.0, and the control group, whose index was <9.0. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…We also demonstrated that urinary pooling inside the urethra evaluated by postoperative MRI might induce urgency 4 . In addition, patients with arteriosclerosis reportedly have persistence of OAB symptoms after RARP, and de novo OAB reportedly occurs to a greater extent in patients with arteriosclerosis than those without it 5 . Consequently, there is concern regarding the association between the mRUL and OAB symptoms, and additional clarification of this association is awaited.…”
mentioning
confidence: 79%
“…We also demonstrated that urinary pooling inside the urethra evaluated by postoperative MRI might induce urgency 4 . In addition, patients with arteriosclerosis reportedly have persistence of OAB symptoms after RARP, and de novo OAB reportedly occurs to a greater extent in patients with arteriosclerosis than those without it 5 . Consequently, there is concern regarding the association between the mRUL and OAB symptoms, and additional clarification of this association is awaited.…”
mentioning
confidence: 79%
“…Therefore, many papers regarding PRO after RARP have already been published. [1][2][3][4] In the present study, Kohada et al divided patients who underwent RARP into a high-interest in sex group and a lowinterest in sex group on the basis of attempts for penile rehabilitation. 5 The authors evaluated urinary function, urinary trouble, sexual function, and sexual trouble using the expanded prostate cancer index composite questionnaire.…”
Section: Editorial Commentmentioning
confidence: 94%
“…Thus, patient reported outcomes (PRO) concerning their health‐related QOL are considered as important as screening for the recurrence of prostate cancer. Therefore, many papers regarding PRO after RARP have already been published 1–4 …”
mentioning
confidence: 99%
“…Even in the era of robotic surgery, there is still a constant percentage of patients with urinary incontinence (UI) and overactive bladder (OAB) symptoms after radical prostatectomy (RP) . Several studies investigated the associations between UI or OAB symptoms after RP and preoperative or postoperative membranous urethral length (MUL) .…”
Section: Introductionmentioning
confidence: 99%
“…Even in the era of robotic surgery, there is still a constant percentage of patients with urinary incontinence (UI) and overactive bladder (OAB) symptoms after radical prostatectomy (RP). [1][2][3][4] Several studies investigated the associations between UI or OAB symptoms after RP and preoperative or postoperative membranous urethral length (MUL). [5][6][7][8][9][10] These previous studies independently investigated only the associations between UI or OAB symptoms and preoperative or postoperative MUL.…”
Section: Introductionmentioning
confidence: 99%